Iron cycling in the anoxic cryo-ecosystem of Antarctic Lake Vida - Proemse, B.; Murray, A.; Schallenberg, C.; McKiernan, B.; Glazer, B.; Young, S.; Ostrom, N.; Bowie, A.; Wieser, M.; Kenig, F.; Doran, P.; Edwards, Peter (Springer Netherlands, 2017)
© 2017, Springer International Publishing Switzerland. Iron redox cycling in metal-rich, hypersaline, anoxic brines plays a central role in the biogeochemical evolution of life on Earth, and similar brines with the potential to harbor life are thought to exist elsewhere in the solar system. To investigate iron biogeochemical cycling in a terrestrial analog we determined the iron redox chemistry and isotopic signatures in the cryoencapsulated liquid brines found in frozen Lake Vida, East Antarctica. We used both in situ voltammetry and the spectrophotometric ferrozine method to determine iron speciation in Lake Vida brine (LVBr). Our results show that iron speciation in the anoxic LVBr was, unexpectedly, not free Fe(II). Iron isotope analysis revealed highly depleted values of -2.5‰ for the ferric iron of LVBr th at are similar to iron isotopic signatures of Fe(II) produced by dissimilatory iron reduction. The presence of Fe(III) in LVBr therefore indicates dynamic iron redox cycling beyond iron reduction. Furthermore, extremely low d 18 O–SO 4 2- values (-9.7‰) support microbial iron-sulfur cycling reactions. In combination with evidence for chemodenitrification resulting in iron oxidation, we conclude that coupled abiotic and biotic redox reactions are driving the iron cycle in Lake Vida brine. Our findings challenge the current state of knowledge of anoxic brine chemistry and may serve as an analogue for icy brines found in the outer reaches of the solar system.